A family with both X‐linked dominant Charcot–Marie–Tooth disease and myotonic dystrophy type 1 mutations with phenotypic variations. Issue 2 (19th November 2018) - Mori, Chiaki; Nakatani, Rie; Nakamori, Masayuki; Matsumura, Tsuyoshi; Takahashi, Masanori P.; Fujimura, Harutoshi; Mochizuki, Hideki; Sakoda, Saburo
Abstract: We report 2 members of a family with gene mutations for both X‐linked dominant Charcot–Marie–Tooth disease and myotonic dystrophy type 1. The father shows symptoms of hereditary motor and sensory neuropathy, while his daughter has symptoms of myotonic dystrophy. Detailed clinical manifestations in both cases are described.